APLIKASI PENDUKUNG KEPUTUSAN PENERIMA BEASISWA CSR MENGGUNAKAN METODE WEIGHT PRODUCT (WP) - Bunga Intan; Muhammad Irvai; Nolan Efranda (P3M Institut Teknologi Pagar Alam, 2023)
The problem with this research is that in the process of selecting CSR scholarship recipients it is still done manually by filling out the exam sheets that have been provided, then the marketing unit returns to manually record the value data. Applications created using the codeigniter framework programming language are integrated with the Weight Product (WP) method and MySQL Improved as database management. The life flow model used in making this application is the waterfall method. With an online-based Corporate Social Responsibility (CSR) scholarship decision support application, it can support decision making regarding acceptance of CSR scholarships by Bina Insan University. The purpose of this application is to make it easier to manage data on prospective scholarship recipients and make it easier to make decisions so that they are faster, accurate and transparent